2009
DOI: 10.1074/jbc.m109.013623
|View full text |Cite
|
Sign up to set email alerts
|

Hypomaturation Enamel Defects in Klk4 Knockout/LacZ Knockin Mice

Abstract: Kallikrein 4 (Klk4) is believed to play an essential role in enamel biomineralization, because defects in KLK4 cause hypomaturation amelogenesis imperfecta. We used gene targeting to generate a knockin mouse that replaces the Klk4 gene sequence, starting at the translation initiation site, with a lacZ reporter gene. Correct targeting of the transgene was confirmed by Southern blot and PCR analyses. Histochemical X-gal (5-bromo-4-chloro-3-indolyl-␤-D-galactopyranoside) staining demonstrated expression of ␤-gala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
186
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(202 citation statements)
references
References 81 publications
14
186
0
2
Order By: Relevance
“…These data support the acid hypothesis, postulating that the acidic environment of the maturation stage makes ameloblasts more susceptible to the toxic effects of F -exposure. (Simmer et al, 2009). The knock-in LacZ has a nuclear localization signal to help distinguish its expression from endogenous lysosomal β-galactosidase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data support the acid hypothesis, postulating that the acidic environment of the maturation stage makes ameloblasts more susceptible to the toxic effects of F -exposure. (Simmer et al, 2009). The knock-in LacZ has a nuclear localization signal to help distinguish its expression from endogenous lysosomal β-galactosidase.…”
Section: Discussionmentioning
confidence: 99%
“…KLK4 degrades enamel matrix proteins (Ryu et al, 2002) before their export from the hardening enamel . Ablation of Klk4 in mice results in abnormally soft enamel with a higher than normal protein content (Simmer et al, 2009), and fluorosed enamel displays the same characteristics. Previously, we showed that murine Klk4 transcript levels were reduced after F -treatment (Sharma et al, 2010), and here we propose a mechanism by which this occurs and demonstrate that protein levels are similarly affected.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Mouse models for AI have been developed to test the function of the amelogenin protein group, and to begin to define the roles of the individual amelogenin proteins. Mice have been generated to express an overabundance of one amelogenin, to express a mutated amelogenin or to express only one amelogenin, but none of the other amelogenins 24,25,26 .…”
Section: Mouse Models For Amelogenesis Imperfectamentioning
confidence: 99%
“…Similar to human KLK4, the mouse and pig homologues (enamel matrix serine proteinase 1) are required for proper tooth formation (Simmer et al, 2009;Hu et al, 2011). Murine mKLK4 possesses three sequons at Asn109, Asn159, and Asn202; it shares the latter two with porcine pKLK4 that has a third sequon at Asn120 (Figure 2).…”
Section: The Prostatic and Dental Klk4mentioning
confidence: 99%